Cognitive assessment in Multiple Sclerosis: towards the development of a cognitive screening pathway - Elwick, Hannah (2022)
Background It is estimated that as many as 86% of people with Multiple Sclerosis (MS) can experience cognitive impairment, which can impact quality of life. Although the value of screening for cognitive problems is recognised, it is not routinely undertaken.